1977
DOI: 10.1111/j.1432-1033.1977.tb11909.x
|View full text |Cite
|
Sign up to set email alerts
|

Human α‐N‐Acetylglucosaminidase

Abstract: Purified urinary α‐N‐acetylglucosaminidase acts as an exoglycosidase. The enzyme removes from heparan sulfate exclusively α‐glycosidically linked N‐acetylglucosamine residues. The pH optimum of around 4.4 towards heparan sulfate and heparin is similar to that towards synthetic arylglycosides. Urinary α‐N‐acetylglucosaminidase can be separated by isoelectric focusing into multiple forms with pI values between 3.3 and 6.0. The multiple forms differ in their recognition and endocytosis by cultivated skin fibrobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1978
1978
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…a-L-iduronidase [23], arylsulphatase B [35,36], a-N-acetylglucosaminidase [37], sulphoiduronate sulphohydrolase (J. Bielicki, P. R. Clements & J. J. Hopwood, unpublished work) and ,-N-acetylhexosaminidase [38]} or in the degradation of other glycoconjugates [39,40] have been reported. Cheng et al [40] purified and identified two forms of cx-D-mannosidase from human liver that differed in both their subunit composition and their ability to be taken up into cultured human skin fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…a-L-iduronidase [23], arylsulphatase B [35,36], a-N-acetylglucosaminidase [37], sulphoiduronate sulphohydrolase (J. Bielicki, P. R. Clements & J. J. Hopwood, unpublished work) and ,-N-acetylhexosaminidase [38]} or in the degradation of other glycoconjugates [39,40] have been reported. Cheng et al [40] purified and identified two forms of cx-D-mannosidase from human liver that differed in both their subunit composition and their ability to be taken up into cultured human skin fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that this enzyme acts optimally under intestinal conditions (pH 7.0 -7.5), which are noticeably different from the optimal conditions of human ␣GNase (i.e. pH 4.5-5.0), a lysosomal glycosidase (18,19).…”
Section: Molecular Cloning and Expression Of Full-length And Truncatementioning
confidence: 69%
“…Since these residues are unique to heparan sulfate and heparan, it is plausible that deficiency of each of these enzymes results in the intralysosomal storage of heparan sulfate-like fragments and their increased urinary excretion. At their non-reducing terminals these fragments bear predominantly N-sulfoglucosaminyl residues (Sanfilippo type A), N-acetylglucosaminyl residues (Sanfilippo type B) or glucosaminyl residues (Sanfilippo type C) (Kresse et al, 1977;von Figura, 1977).…”
Section: Discussionmentioning
confidence: 99%